New view on alcoholic liver disease - potential role of PD1/PDL-1 pathway in the disease pathogenesis - Adamczyk, Katarzyna; Kasztelan-Szczerbińska, Beata; Rycyk, Anna; Cichoż-Lach, Halina (Journal of Education, Health and Sport, 2019)
Introduction: Exposure to chronic, excessive alcohol consumption, its breakdown metabolites, and gut-derived endotoxins dysregulate immune signaling leading to activation of inflammation. As a result, the non-resolving inflammatory response and development of alcoholic liver disease (ALD) may occur. There are still no pharmacological or nutritional therapies for treating patients with alcoholic liver disease. Material and Methods: The information provided was collected as a result of various article’s analyses on the development, diagnosis, and treatment of patients with alcoholic liver disease using Google Scholar and PubMed databases. Results: The pathway consisting of the programmed cell death 1 (PD-1) receptor and its ligand PD-L1 may play a critical role in the inhibition of self-reactive and inflammatory effector cells and the protection against immune-mediated tissue damage. There is a possibility of the potential gender-related differences in PD1/PD-L1 signaling in ALD. Conclusion: The better understanding of ALD as a dynamic process and all aspects of immune dysregulation may be important for the development of novel therapies in alcoholic liver disease. Results from a further study on the PD1/PDL-1 pathway might be exploited to re-define therapeutic targets and create sex-tailored treatments according to individual patient needs.